Large-scale synthesis of high quality InP quantum dots in a continuous flow-reactor under supercritical conditions. (6th February 2015) - Ippen, Christian; Schneider, Benjamin; Pries, Christopher; Kröpke, Stefan; Greco, Tonino; Holländer, Andreas
Abstract: The synthesis of indium phosphide quantum dots (QDs) in toluene under supercritical conditions was carried out in a macroscopic continuous flow reaction system. The results of first experiments are reported in comparison with analogous reactions in octadecene. The reaction system is described and details are provided about special procedures that are enabled by the continuous flow system for the screening of reaction conditions. The produced QDs show very narrow emission peaks with full width at half maximum down to 45 nm and reasonable photoluminescence quantum yields. The subsequent purification process is facilitated by the ease of removal of toluene, and the productivity of the system is increased by high temperature and high pressure conditions.